Evaluation of Bio-Control Agents against Fusarium Wilt of Cucumber - Sharma, Deepika; Shukla, Arti; Gupta, Meenu (International Journal of Economic Plants, 2022)
The experiment was carried out in Department of Plant Pathology, Dr Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh, India during cropping season of May to August in year 2018–2019 to study the efficacy of fungal and bacterial bio-control agents in managing the Fusarium wilt of cucumber. Different fungal and bacterial bio-control agents were thus tested under laboratory conditions for their efficacy in inhibiting the mycelial growth of Fusarium oxysporum by using dual culture technique and streak plate method, respectively. Among fungal bio-control agents, Trichoderma harzianum was found most effective with 61.08% inhibition of mycelial growth of F. oxysporum followed by Trichoderma virens with 57.51% mycelial inhibition whereas, among bacterial bio-control agents, maximum mycelial inhibition of 45.69% was observed in Pseudomonas fluorescens. During the cropping season, seed, and soil treatment with effective fungal and bacterial bioagents was carried out under field conditions. Seed treatment and soil application of Trichoderma harzianum was found effective with disease control of 48.25% followed by Trichoderma virens which is proved to be efficacious with 42% disease control against Fusarium wilt of cucumber.